Genotoxicity study of high aspect ratio silver nanowires. Issue 5 (3rd July 2017) - Charehsaz, Mohammad; Coskun, Sahin; Unalan, Husnu Emrah; Reis, Rengin; Helvacioglu, Sinem; Giri, Ashok Kumar; Aydin, Ahmet
ABSTRACT: The genotoxicity potential of silver nanowires synthesized via the solution-based polyol method has been investigated. They were found to be non-mutagenic in three Salmonella strains and were not genotoxic in a clastogenicity assay in mice. Residual surfactant was found to have an effect on the toxicological properties of the nanowires by increasing the rate of Ag + release. Residual surfactant can be easily degraded via a UV treatment.